2005
DOI: 10.1007/s10236-005-0028-z
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of river discharge and tidal modulation in a tropical estuary, NE Brazil

Abstract: Observations of thermohaline properties and currents were undertaken in the Curimatau´River estuary (6°18¢S), Rio Grande do Norte state (RN), Brazil, during consecutive neap-spring tidal cycles in the austral autumn rainy season. Highly asymmetric neap tide along channel velocities (À0.4 to 0.9 m s À1 ) and highly stratified conditions were generated by an increase of the buoyancy energy from the freshwater input (R iE %5.6). During the spring-tidal cycle the river discharge decreased and the longitudinal velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 11 publications
3
12
0
6
Order By: Relevance
“…This behaviour was observed by Miranda et al (2005), in a study performed in the Curimataú River, where the author shows that the salinity ranges from 20 to 36 in the period of major fluvial discharges and from 30·2 to 30·7 in the dry season. This behaviour shows a major amplitude in the variation of salinity, showing an increased influence of coastal waters (CW) during periods of lower fluvial discharges (dry season).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…This behaviour was observed by Miranda et al (2005), in a study performed in the Curimataú River, where the author shows that the salinity ranges from 20 to 36 in the period of major fluvial discharges and from 30·2 to 30·7 in the dry season. This behaviour shows a major amplitude in the variation of salinity, showing an increased influence of coastal waters (CW) during periods of lower fluvial discharges (dry season).…”
Section: Resultssupporting
confidence: 71%
“…The tidal co‐oscillation at the estuaries' mouths is classified as meso‐tidal and semi‐diurnal according to its height and periodicity, respectively, ranging between 1·1–1·4 and 1·8–2·0 m in neap and spring‐tide periods, for the Contas and Jaguaribe Rivers, respectively (Dias, 2007; Dias et al , 2007). Many studies conducted in tropical estuaries (Cunha, 1982; Medeiros and Kjerfve, 1993; Araujo, et al , 1999; Miranda et al , 2005) observed a higher tidal influence during dry period, where the estuaries were controlled for a semi‐diurnal barotropic tide. Nicolite et al (2009) observed that during lower discharges water level variation in the estuarine channel is due to the co‐oscillation of the astronomical tides and/or meteorological tides in the estuary of the Paraiba do Sul River.…”
Section: Resultsmentioning
confidence: 99%
“…A similar effect was found by [13] in studying the dynamics of a tropical estuary, the Curimataú River, Brazil.…”
Section: Discussionsupporting
confidence: 57%
“…Beyond isopycnic 20 (s θ ≥20), there was a marked presence of the coastal water masses (CW). This type of distribution was described by Miranda et al (1998Miranda et al ( , 2002Miranda et al ( , 2005 as a classical distribution of water masses in estuarine systems. Table 3 Values of temperature (1C) and salinity characteristics of the respective water masses observed in the study area.…”
Section: Minimummentioning
confidence: 89%